The Relationship Between Perceived Organizational Support With Job Embeddedness in Employees of Waterboom Pesona Modern Banjarmasin - Lailasari, Noor; Dewi, Rooswita Santia; Akbar, Sukma Noor (Jurnal Kognisia, 2021)
Every company requires its employees as personnel to perform every activity in the organization of a company. An ideal organization or company must have long-term and short-term goals because these goals are the basis of an organization. One of the long term goals is how to keep employees staying in a company. Job embeddedness is a totality of employees which is psychologically, socially, and financially influenced by the organization and community that affects the choice individuals make to remain with a job. The employees with high job embeddedness, who feel that they have a bond and an attachment financially to their company, will choose to stay in their job. The treatment and relationship received by the employees in the organization are interpreted as perceived organizational support. Perceived organizational support is the employees' global belief about the extent to which the organization cares about their well-being and values their contributions. That the employees feel there is organizational support will have a positive impact in the form of the employees’ attitudes and behaviors that can help the company achieve its goals. The purpose of this study was to find out whether there was a relationship between perceived organizational support and job embeddedness in employees of Waterboom Pesona Modern Banjarmasin. The samples in this study were 52 employees who were selected using a total sampling technique. Based on the analysis test, it was found that there was a positive correlation between perceived organizational support and job embeddedness. It can therefore be concluded that the higher the perceived organizational support, the higher the level of job embeddedness in the employees and vice versa. Keywords: perceived organizational support, job embeddedness, employee